Plasma concentrations of advanced glycation end-products and colorectal cancer risk in the EPIC study. (29th March 2021) - Aglago, Elom K; Schalkwijk, Casper G; Freisling, Heinz; Fedirko, Veronika; Hughes, David J; Jiao, Li; Dahm, Christina C; Olsen, Anja; Tjønneland, Anne; Katzke, Verena; Johnson, Theron; Schulze, Matthias B; et al.
Abstract: Advanced glycation end-products (AGEs) are a heterogeneous group of compounds formed by the non-enzymatic reaction between amino acids and reducing sugars, or dicarbonyls as intermediate compounds. Experimental studies suggest that AGEs may promote colorectal cancer, but prospective epidemiologic studies are inconclusive. We conducted a case–control study nested within a large European cohort. Plasma concentrations of three protein-bound AGEs—N ε -(carboxy-methyl)lysine (CML), N ε -(carboxy-ethyl)lysine (CEL) and N δ -(5-hydro-5-methyl-4-imidazolon-2-yl)-ornithine (MG-H1)—were measured by ultra-performance liquid chromatography–tandem mass spectrometry in baseline samples collected from 1378 incident primary colorectal cancer cases and 1378 matched controls. Multivariable-adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were computed using conditional logistic regression for colorectal cancer risk associated with CML, CEL, MG-H1, total AGEs, and [CEL+MG-H1: CML] and [CEL:MG-H1] ratios. Inverse colorectal cancer risk associations were observed for CML (OR comparing highest to lowest quintile, ORQ5 versus Q1 = 0.40, 95% CI: 0.27–0.59), MG-H1 (ORQ5 versus Q1 = 0.73, 95% CI: 0.53–1.00) and total AGEs (OR Q5 versus Q1 = 0.52, 95% CI: 0.37–0.73), whereas no association was observed for CEL. A higher [CEL+MG-H1: CML] ratio was associated with colorectal cancer risk (ORQ5 versus Q1 = 1.91, 95% CI: 1.31–2.79). The associations observed did not differ by sex, or by tumour anatomical sub-site. Although individual AGEs concentrations appear to be inversely associated with colorectal cancer risk, a higher ratio of methylglyoxal-derived AGEs versus those derived from glyoxal (calculated by [CEL+MG-H1: CML] ratio) showed a strong positive risk association. Further insight on the metabolism of AGEs and their dicarbonyls precursors, and their roles in colorectal cancer development is needed. Abstract : We evaluated colorectal cancer risk associated with blood levels of major advanced glycation end-products (AGEs). The AGEs examined were mostly associated with lower colorectal cancer risk. The ratio of methylglyoxal-derived versus glyoxal-derived AGEs was positively associated with colorectal cancer.